Radioactive Iodine Therapy Decreases Recurrence in Thyroid Papillary Microcarcinoma. (7th March 2012) - Creach, Kimberly M.; Siegel, Barry A.; Nussenbaum, Brian; Grigsby, Perry W.
Abstract : Background . The most appropriate therapy for papillary microcarcinoma (PMC) is controversial. Methods . We reviewed the therapy and outcome of 407 patients with PMC. Results . Three hundred-eighty patients underwent total thyroidectomy, and 349 patients received I-131 therapy. The median followup was 5.3 years. Forty patients developed recurrent disease. On univariate analysis, development of disease recurrence was correlated with histological tumor size > 0.8 cm (P = 0.0104 ), age < 45 years (P = 0.043 ), and no I-131 therapy (P < 0.0001 ). On multivariate analysis, histological tumor size > 0.8 cm, positive lymph nodes, and no I-131 therapy were significant. The 5-year RFS for patients treated with I-131 was 95.0% versus 78.6% (P < 0.0001 ) for patients not treated with I-131. Patients with lymph node metastasis who did not receive I-131 had a 5-year RFS of 42.9% versus 93.2% (P < 0.0001 ) for patients who received I-131. Conclusions . Recommend I-131 remnant ablation for patients with PMC, particularly patients with lymph node metastasis.